2020
DOI: 10.4314/ijbcs.v14i7.17
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation de la fertilité des sols et les rendements de cotonnier, maïs et sorgho à >Gliricidia sepium (Jacq.) Kunth ex. Walp

Abstract: De nos jours, la carence en fertilité des sols est un problème très répandu dans la plupart des pays subsahariens. G. sepium a été testé en association avec le cotonnier, le maïs et le sorgho afin de développer les meilleures pratiques dans deux stations de recherche et en milieu paysan dans les zones soudaniennes et soudano-guinéenne du Mali. L'objectif de cette étude était de développer, avec les producteurs participants, une technologie agro-forestière basée sur le Gliricidia sepium dans le système de cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
2
0
2
Order By: Relevance
“…These results can be attributed to the nitrogen use efficiency of 22 kg of sorghum grain per kg of nitrogen with the application of the compost microdose at 2.5 t ha −1 + 100 kg ha −1 DAP, compared to only 8 kg of grain per kg of nitrogen with the application of 5 t ha −1 + 100 kg ha −1 DAP. The application of 56.25 g of compost per plant hole ensures a concentrated supply of nutrients to the plants, reduces losses [33,34], and improves the chemical, physical, and biological properties of soils for subsequent crops in the rotation [35,36]. Although the benefits of microdosing have been demonstrated by several studies [29,37], we found that its contribution to the soil fertility restoration, especially nitrogen (N), was less than that of the application of 5 t ha −1 by broadcasting.…”
Section: Sustainability Of the Production Systemmentioning
confidence: 99%
“…These results can be attributed to the nitrogen use efficiency of 22 kg of sorghum grain per kg of nitrogen with the application of the compost microdose at 2.5 t ha −1 + 100 kg ha −1 DAP, compared to only 8 kg of grain per kg of nitrogen with the application of 5 t ha −1 + 100 kg ha −1 DAP. The application of 56.25 g of compost per plant hole ensures a concentrated supply of nutrients to the plants, reduces losses [33,34], and improves the chemical, physical, and biological properties of soils for subsequent crops in the rotation [35,36]. Although the benefits of microdosing have been demonstrated by several studies [29,37], we found that its contribution to the soil fertility restoration, especially nitrogen (N), was less than that of the application of 5 t ha −1 by broadcasting.…”
Section: Sustainability Of the Production Systemmentioning
confidence: 99%
“…This increase may be due to: the added organic manure at establishment (at a rate of 2.500 kg/ha), input of leaf litter, root turnover and potentially higher levels of soil microbes (Bernoux and Chevalier 2013). The study by Doumbia et al (2020) in Mali showed that planting Gliricidia sepium in the corridor increased the organic carbon and total nitrogen content in the soils between the alleys by 5% after three years. Similarly, this study also showed that the application of mulch produced from Gliricidia sepium on crops allowed to maintain and improve the physical and chemical properties of soils ( sequestration in soils.…”
Section: Fodder Chemical Composition Of Leucaena Leucocephala and Mor...mentioning
confidence: 99%
“…Cependant, les sols utilisés pour leur production sont naturellement pauvres en éléments nutritifs nécessaires au développement harmonieux des plantes (Somda et al, 2017). En plus, les effets conjugués de pratiques agricoles inappropriées et des effets négatifs du changement climatique menacent la production agricole en zone sahélienne (Doumbia et al, 2020). Bien que les engrais minéraux soient efficaces pour augmenter les rendements des cultures, leur utilisation dans cette région Afrique subsaharienne reste faible.…”
Section: Introductionunclassified